Inside Cover: Iodine‐Catalysed Dissolution of Elemental Gold in Ethanol (Angew. Chem. Int. Ed. 14/2022). Issue 14 (9th March 2022) - Zupanc, Anže; Heliövaara, Eeva; Moslova, Karina; Eronen, Aleksi; Kemell, Marianna; Podlipnik, Črtomir; Jereb, Marjan; Repo, Timo
Abstract : Gold is a valuable metal that can be dissolved with common household chemicals as reported by Timo Repo et al. in their Research Article (e202117587) . By applying catalytic iodine, aqueous hydrogen peroxide and 2‐mercaptobenzimidazole, gold promptly dissolves in ethanol. Catalytic reactions and environmentally benign solvents and reagents are the basis for sustainable development and a gateway to a greener future of precious metals recycling.